(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate certain characteristics of patients and management outcomes of postpartum hemorrhage (PPH) following cesarean section in in vitro fertilization (IVF) pregnancies at the National Hospital of Obstetrics and Gynecology during 2023–2024. Methods: A cross-sectional descriptive study. Results: There were 74 cases of IVF-associated PPH after cesarean section. The mean maternal age was 35,16 years; the rate of multiple pregnancies was 37,84 %; frozen embryo transfer accounted for 87,8 %; and elective cesarean section accounted for 86,5% of cases. The main causes of PPH were uterine atony (70,27%), placenta previa (18,91%), and placenta accreta (10,81%). Among cases of uterine atony, combined use of uterotonic drugs and uterine artery ligation was applied in 19,23%. For PPH due to placenta previa, the most common management methods were uterotonics with suturing of the bleeding placental site (35,7%) and uterine artery ligation (50%). In cases of placenta accreta, subtotal hysterectomy for hemostasis was performed in 50%. The uterine preservation rate in our study was 89,19%. Conclusion: Management of intraoperative and postoperative hemorrhage after cesarean section in IVF pregnancies requires a multimodal approach depending on the underlying cause.